The Development of Lhokseumawe City during the New Order Period - Isnani Isnani; Suprayitno Suprayitno; Nuhung Nuhung (Warisan: Journal of History and Cultural Heritage, 2024)
This article discusses Lhokseumawe City during the New Order era using historical research methods consisting of heuristics, verification, interpretation and historiography. The research results show that Lhokseumawe City tends to have good geographical conditions as an industrial location. This is also supported by Lhokseumawe's long history as an indicator that this region has long been important to rulers at all times. During the New Order government, Lhokseumawe was then turned into an industrial city with all the natural resources it had. The success of the New Order in turning Lhokseumawe into an industrial city was carried out by enacting Regional Laws and Regulations as legitimacy in the management of all commodities owned by the region. Even though development was promoted in Lhokseumawe, it was only physical, while the people still experienced social inequality, until the end of the New Order's rule for more than 30 years.